A POLITICA DE EDUCAÇÃO NO PERIODO POPULISTA - DESENVOLVIMENTISTA (1945 - 1964) - Aline Linares de Oliveira Scandelai (Universidade do Oeste Paulista, 2011)
This article examines the posture and the importance of education in the management of Presidents of the Republic to govern Brazil for the years1945 to 1964, a period in history called "populist-development", highlighted the achievements, as the realization the first Law of Directives and Bases of Education, and disappointments, as almost half a decade without any investment in the education system. The four initial years of the new term of Vargas are kept populism, the development of industry, petroleum; there is incentive to work, education and assistance. A complaint must be made: there is no attention to rural workers during the present government. The management of Juscelino Kubitschek main attraction foreign capital. There is an incentive for the Northeast and the construction of Brazil capital: Brasilia. An unfavorable aspect to this government is the neutralization of social policies. The managements of Quadros and Goulart bases have solidified into socialism. There is an economic stagnation and inflation at the time marked, but they have incentives to work, education and Social Security. The downside is no attention to rural and domestic workers.